The Relationship between Different Dimensions of Organizational justice and Organizational Entrepreneurship in Small Firms - Morad Rezai Dizgah; Hamidreza Alipour; Askar Rahimi Dinachali (مدیریت بهره وری, 2011)
Today, the discussion of globalization and increasing competition, quality, etc. has created new challenges for the governments and organizations. One of the ways to cope with these challenges is resorting to entrepreneurship and developing it through small firms which, with their specific characteristics, have a significant role in the economy of the countries. Studies indicate that these companies, too, are faced with problems in their activities. On the other hand, entrepreneurship is carried out by the human power of the organization, and one of the topics that has always accompanied human beings is the discussion of justice. The study of justice in organizations, which is called organizational justice, consists of four dimensions, namely distributional justice, procedural justice, interpersonal justice, and informational justice. In this research, organizational entrepreneurship and organizational justice are considered as the independent and dependent variables, respectively, and the relationship between each of the organizational justice dimensions and the organizational entrepreneurship has been tested. The results of testing the hypotheses show that all the four dimensions of organizational justice have a significant and positive relationship with organizal entrepreneurship in these firms, and some suggestions have been presented in this regard.